The Effect of Digital Fatigue on the Quality of Managerial Decision-Making in Digital Platform-Based SMEs - Miftahurrohman Miftahurrohman; Dhevi Dadi Kusumaningtyas (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2024)
The rapid expansion of digital platforms has transformed managerial practices in small and medium-sized enterprises (SMEs), yet prolonged exposure to digital technologies increasingly raises concerns regarding digital fatigue and its consequences for decision quality. This study aims to examine the effect of digital fatigue on the quality of managerial decision-making among digital platform-based SMEs and to clarify the cognitive and emotional mechanisms underlying this relationship. Using a mixed-methods sequential explanatory design, quantitative data were collected from 150 SME owners and managers through structured questionnaires and analyzed using SEM-PLS, while qualitative insights were obtained from in-depth interviews with 10 key informants conducted during the 2023-2025 period. The findings reveal a significant negative effect of digital fatigue on managerial decision quality, indicating that higher levels of cognitive exhaustion, emotional instability, and attentional overload reduce accuracy, rationality, and consistency in business decisions. Qualitative evidence further shows that intensive multitasking, continuous notifications, and prolonged screen exposure weaken analytical judgment and increase reliance on intuition. This study contributes theoretically by integrating psychological fatigue into models of managerial decision-making in digital entrepreneurship, and practically by emphasizing the importance of digital workload management to sustain effective leadership in technology-driven SMEs.